[Cu]-Catalyzed S(N)AR reactions: direct amination of electron deficient aryl halides with sodium azide and the synthesis of arylthioethers under Cu(II)-ascorbate redox system - Goriya, Yogesh; Ramana, C. V. (Tetrahedron, 2010)
A one pot [Cu]-promoted SNAr reaction of electron-deficient halobenzenes with sodium azide and the reduction of the intermediate aryl azides under the same Cu(II) ascorbate redox conditions leading to anilines has been documented. Control experiments revealed that both ascorbate and proline play important role in the reaction path way. Further, the use of this catalytic Cu(II) ascorbate redox system has been explored for the synthesis of arylthioethers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Anilines; Azide reduction; Cu(II)-ascorbate redox system; SNAr reaction; Thioether